'Blind laws' and the bureaucracy of rights migrant industrial workers in post‐lockdown India. (7th June 2021) - Ruthven, Orlanda
Abstract: After a traumatic lockdown in 2020, India's migrant factory workers have headed back to work and on worse terms than before. Struggling with new levels of denial of entitlements, workers respond by withdrawing from their fragile hold on formality, moving instead further into the informal sector. Based on voice notes recorded on Saajha Manch, a phone‐based community media platform, the paper examines workers' experience that their efforts to claim their rights lure them into a quagmire in a bureaucracy which sucks their energy while assuring no clear outcome. Seeing evidence of failed enforcement and structural inequality all around them, workers conclude that the law is not meant for them and hence show little interest in the new labour codes hastily enacted at the height of the pandemic. The paper highlights the dysfunction of the formal sector in delivering to its low‐waged workers who remain unserved in spite of registration and documentation in place. As they join the ranks of informality, however, migrant factory workers do not lose interest in associative and contentious activity. On the contrary, freedom from the bureaucracy of rights may be a boost to new forms of struggle.